Pengaruh Student's Knowledge about Environmental Issues dan Locus of Control terhadap Citizenship Behavior toward Environment Peserta Didik di SMAN Jakarta - Anisa Fitriani; I Made Putrawan; Daniar Setyo Rini (IJEEM - Indonesian Journal of Environmental Education and Management, 2023)
In the current era of globalization there has been an increase in criminality in the environmental sector that must be resolved by increasing citizenship behavior toward the environment. The aim of this research is to know the effect of students' knowledge about environmental issues and locus of control on citizenship behavior. This research was conducted at SMA X Jakarta with 100 students as a sample. The method used is survey method through causal studies with path analysis. The results of the path analysis show that (1) student's knowledge about environmental issues does not have a direct effect on citizenship behavior on 0.131; (2) locus of control has a direct effect on citizenship behavior on 0.242; (3) student's knowledge about environmental issues has a direct effect on citizenship behavior on 0.388; (4) student's knowledge about environmental issues doesn’t have an indirect effect on citizenship behavior through locus of control.